2022
DOI: 10.1128/spectrum.01542-22
|View full text |Cite
|
Sign up to set email alerts
|

2 E ,4 E -Decadienoic Acid, a Novel Anti-Oomycete Agent from Coculture of Bacillus subtilis and Trichoderma asperellum

Abstract: P . nicotianae is an oomycete pathogen that is destructive to crops. Although some oomycete inhibitors have been used during crop production, most are harmful to the ecology and lead to pathogen resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…Interestingly, the most significant improvement was observed in the co-culture of E. amstelodami and B. licheniformis, indicating that several silenced Sun et al, 2022). In recent years, many research reported that Bacillus species was an ideal strain for establishing co-culture systems, on the one hand, Bacillus species, as a representative of biocontrol microorganisms, the co-culture of Bacillus species and other biocontrol microorganisms exhibited stronger inhibition of plant pathogenic microorganisms and promoted plant growth (Karuppiah et al, 2019;Liu H. et al, 2022), on the other hand, the co-culture of Bacillus species and other microorganisms could markedly increase the production of SMs contained multibiological activity (Sun et al, 2022;Zhang X. F. et al, 2022). However, due to the randomness of microbial co-culture as well as the structural complexity of SMs, many potentially promising microbial co-culture combinations remain undiscovered.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the most significant improvement was observed in the co-culture of E. amstelodami and B. licheniformis, indicating that several silenced Sun et al, 2022). In recent years, many research reported that Bacillus species was an ideal strain for establishing co-culture systems, on the one hand, Bacillus species, as a representative of biocontrol microorganisms, the co-culture of Bacillus species and other biocontrol microorganisms exhibited stronger inhibition of plant pathogenic microorganisms and promoted plant growth (Karuppiah et al, 2019;Liu H. et al, 2022), on the other hand, the co-culture of Bacillus species and other microorganisms could markedly increase the production of SMs contained multibiological activity (Sun et al, 2022;Zhang X. F. et al, 2022). However, due to the randomness of microbial co-culture as well as the structural complexity of SMs, many potentially promising microbial co-culture combinations remain undiscovered.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of pepper phytophthora blight, the inoculum of Ph. capsici and the diseased soil were prepared according to the method described by Zhang et al (2022) . Briefly, millet was sterilized after being boiled for 30 min and inoculated with Ph.…”
Section: Methodsmentioning
confidence: 99%
“…capsici and the diseased soil were prepared according to the method described by Zhang et al (2022). 23 Briefly, millet was sterilized after being boiled for 30 min and inoculated with Ph. capsici, followed by incubation at 25 °C for 10 days.…”
Section: Methodsmentioning
confidence: 99%
“…KEGG highly enriched pathways include “valine, leucine, and isoleucine degradation” (map00280), “peroxisome” (map04146), “fatty acid degradation” (map00071), “propanoate metabolism” (map00640), “longevity regulating pathway-multiple species” (map04213), and “pyruvate metabolism” (map00620). Relevant studies have shown that these pathways were associated with energy and material metabolism, redox processes, biofilms, and genetic information . Through cluster analysis, it was found that the related DEGs of P.…”
Section: Ph- and Pectinase-responsive Release Behaviors Of Hon From Scrpmentioning
confidence: 99%
“…Relevant studies have shown that these pathways were associated with energy and material metabolism, redox processes, biofilms, and genetic information. 44 Through cluster analysis, it was found that the related DEGs of P. nicotianae treated with SCRP had significant changes in oxidative stress, membrane stability, and material energy metabolism (Figure 4C).…”
Section: Ph-and Pectinase-responsive Release Behaviors Of Hon From Scrpmentioning
confidence: 99%